2021
DOI: 10.1177/0193945920986788
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Diet and Sleep Duration in Different Menopausal Stages

Abstract: This study aimed to determine which dietary factors were associated with habitual sleep duration in pre/peri- and post-menopausal women. Data from the 2007–2008 National Health and Nutrition Examination Survey were used ( N = 1,783). Habitual sleep duration was categorized as very short (<5 h), short (5–6 h), normal (7–8 h), and long (≥9 h). Diet assessment was performed following validated procedures. In pre/peri-menopausal women ( n = 1,116), controlling for the confounders, fewer number of foods, less in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…One research determined an association between short sleep duration and a prevalence of inadequate intake of calcium, magnesium and vitamins A, C, D and E among women ( n = 26211) (Ikonte et al , 2019). In another study, lower intakes of protein, carbohydrate, thiamine, folate, phosphorus, sodium, potassium and selenium were significantly associated with a higher risk of very short sleep in premenopausal women ( n = 1116), and higher sugar intake and lower phosphorus and zinc intakes were associated with a higher risk of short sleep in postmenopausal women ( n = 667) (Zhu et al , 2021). These studies have focused on different sample groups than ours, and there is no research with a similar methodology, involving health-care workers and shift work.…”
Section: Discussionmentioning
confidence: 99%
“…One research determined an association between short sleep duration and a prevalence of inadequate intake of calcium, magnesium and vitamins A, C, D and E among women ( n = 26211) (Ikonte et al , 2019). In another study, lower intakes of protein, carbohydrate, thiamine, folate, phosphorus, sodium, potassium and selenium were significantly associated with a higher risk of very short sleep in premenopausal women ( n = 1116), and higher sugar intake and lower phosphorus and zinc intakes were associated with a higher risk of short sleep in postmenopausal women ( n = 667) (Zhu et al , 2021). These studies have focused on different sample groups than ours, and there is no research with a similar methodology, involving health-care workers and shift work.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study of 769 postmenopausal women showed that a lower diet quality is associated with the lowest quality of sleep, as well as high fat consumption is associated with restless sleep [ 68 ]. The National Health and Nutrition Examination Survey ( N = 1783) showed that postmenopausal women with more sugar intake and lack phosphorus and zinc are associated with short sleep duration [ 69 ]. Finally, a very recent cross-sectional study in 100 postmenopausal women with obesity showed that legume consumption was associated with lower menopausal symptom severity (evaluated with the Menopausal Rating Scale) while extra virgin olive oil consumption was associated with lower psychological symptoms [ 70 ].…”
Section: Nutritional Approach To Women With Menopause and Obesity And...mentioning
confidence: 99%